Criminalization of Human Trafficking; Assessment of Victims in Judges' Verdict for Deviant Sex services - Djoko Sumaryanto (Faculty of Law, University of Mataram, 2020)
The current criminal law still adheres to the concept of Daad Dader Strafrecht, therefore, the existence of crime victims could not betouched by the law which implemented in every judge's decision,such as the event that a husband sells his wife for sex or threesome,the wife position here as the victim, this research was done by using legal research of normative law,which applies statute approach and case approach, by examining Sidoarjo State Court Verdict Number: 889/Pid.Sus/2018/PN.SDA, and it obtained several results, first inaccurate application of law and weak point of views of victim of crime. It can be concluded that after examination of legal facts, review the literatures and analyze it based on the cases, this work suggest husband activities on selling his wife by illegal sex/threesome should not be included as human trafficking. Since normatively, it is not relevant, furthermore the condition of family is not really well.